PRODUKSI BIOLISTRIK OLEH KONSORSIUM BIKULTUR BAKTERI TERMOFILIK MENGGUNAKAN KONFIGURASI FERMENTOR RANGKAIAN SERI PADA MICROBIAL FUEL CELL - Irdawati; Hendriany, Shintia (Jurnal Biogenerasi, 2025)
The increasing global energy demand and the negative impact of the use of fossil energy on the environment encourage the use of environmentally friendly renewable energy sources, one of which is through Microbial Fuel Cell technology. This study aims to measure or analyze bioelectrical production by utilizing a consortium of thermophilic bacterial bicultures (SSA 14 and SSA 16) in an MFC system arranged in a series circuit configuration. The research method was carried out experimentally in the laboratory using a dual-chamber reactor arranged in a series of two and three series, with voltage measurements carried out every 2 hours for 24 hours. The results showed that the series three series produced a higher average voltage (0.823 V) than the series two series (0.744 V). This study indicates that the addition of the number of fermenter units in the series series significantly increases the electrical voltage produced.